2016
DOI: 10.1016/j.neubiorev.2016.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Reward-centricity and attenuated aversions: An adolescent phenotype emerging from studies in laboratory animals

Abstract: Adolescence is an evolutionarily conserved developmental period, with neural circuits and behaviors contributing to the detection, procurement, and receipt of rewards bearing similarity across species. Studies with laboratory animals suggest that adolescence is typified by a “reward-centric” phenotype—an increased sensitivity to rewards relative to adults. In contrast, adolescent rodents are reportedly less sensitive to the aversive properties of many drugs and naturally aversive stimuli. Alterations within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
86
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 217 publications
8
86
2
Order By: Relevance
“…Additionally, although our model did not employ an adult comparison group, previous studies have indicated the structural and functional deficits following intermittent binge EtOH exposure are an adolescent- specific phenomenon (Spear, 2011; Vetreno et al, 2014; Vetreno and Crews, 2015; Crews et al, 2016; Doremus-Fitzwater and Spear, 2016). Previous studies have found that regardless of potential age- related declines in cognition, binge EtOH exposure during adulthood does not typically lead to cognitive flexibility deficits (Coleman et al, 2014; Gass et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, although our model did not employ an adult comparison group, previous studies have indicated the structural and functional deficits following intermittent binge EtOH exposure are an adolescent- specific phenomenon (Spear, 2011; Vetreno et al, 2014; Vetreno and Crews, 2015; Crews et al, 2016; Doremus-Fitzwater and Spear, 2016). Previous studies have found that regardless of potential age- related declines in cognition, binge EtOH exposure during adulthood does not typically lead to cognitive flexibility deficits (Coleman et al, 2014; Gass et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Alcohol exposure during adolescence has been tied to drug abuse vulnerability, as well as disruptions in cognitive functioning (DeWit et al, 2000; Jacobus and Tapert, 2013; Lisdahl et al, 2013). In rodents, exposure to ethanol (EtOH) during early adolescence has been linked to decreased behavioral inhibition and impairments in behavioral flexibility that are sustained into adulthood (Coleman et al, 2014; Gass et al, 2014; Doremus-Fitzwater and Spear, 2016). This distinctive behavioral phenotype results from sustained neural changes in critical brain regions such as the prefrontal cortex (Floresco et al, 2008; Fernandez et al, 2016; Vargas et al, 2014; Liu and Crews, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Both drug addiction and obesity have been suggested to involve similar neurobiological substrates, and may be driven by stronger preferences for or sensitivities to reward [6, 59]. Accordingly, greater reward sensitivity in adolescents may facilitate engagement in maladaptive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…A tendency to assign greater value to reward stimuli may partially contribute to these exaggerated levels of risky reward-seeking behaviors [4, 6]. Greater sensitivity to orosensory reward in adolescent male rats compared to adolescent female rats is interesting, particularly given reports of sex differences in human adolescent risk taking, in which boys tend to be more willing to accept risk than girls [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it has been hypothesized that adolescents are hypersensitive to rewards and that this characteristic of motivated behavior is one of the factors that contributes to heightened vulnerability to developing substance use disorders (Casey et al 2008;Doremus-Fitzwater and Spear 2016;Spear 2000;Steinberg, 2010).…”
Section: Introductionmentioning
confidence: 99%